Strategies used by nurses, academics and students to overcome intercultural communication challenges. Issue 1 (January 2016) - Henderson, Saras; Barker, Michelle; Mak, Anita
Abstract: Nurse clinicians and academics need to understand intercultural communication challenges to improve their communication skills and better support students' learning. Gaps exist in the literature regarding intercultural communication resources for students, academics and clinicians. The aim of this study was to explore the experiences of clinical nurses, nurse academics, and student nurses regarding intercultural communication challenges. Data were collected using focus group interviews with nineteen clinical facilitators (nurses who supervise nursing students in clinical practice), five clinical nurses, and ten nursing students. Seven nurse academics were interviewed via telephone. The purposive sample was drawn from a tertiary hospital and a university in Australia. Participants were invited to discuss challenging intercultural scenarios they had experienced including strategies they used to overcome such challenges. Using qualitative content analysis data were analysed resulting in four categories which were: 1) prejudice based on cultural diversity; 2) unfamiliarity with cultural boundaries; 3) stereotyping cultural behaviours; and 4) difficulty understanding English. Strategies participants used to mitigate challenges included resorting to cultural validation through alliance building, proactively seeking clarification, and acquiring cultural awareness knowledge. This study highlights intercultural challenges students, clinicians and academics face and signpost the way forward with useful strategies to better inform nurse education. Highlights: Participants experienced challenges when experiencing prejudice that impacted negatively on their work practices or learning. Unfamiliarity with cultural boundaries, insufficient cultural education results in misunderstandings, inappropriate behaviour. Stereotyping cultural behaviours led to miscommunication and misinterpreting others actions. Difficulty understanding English resulted in impairment in learning in the classroom/clinical practice. Participants mitigated intercultural communication challenges through cultural validation such as via alliance building.